Pornografia da vingança e a tutela dos direitos fundamentais da vítima - Domingues, Diego Sigoli (2019)
The Information Society, a fundamental right of the fifth dimension, has brought innumerable high technology tools to mankind, especially the internet, which in the year 2011 was recognized by the United Nations as a human right. As a result of the exponential growth of the Internet, numerous positive phenomena have emerged, as well as the facilitation between communication and interaction between people, as negative, highlighting the potential of digital crimes and new forms of contemporary violence, such as pornography of revenge. Inadequate use of the network, often caused by the absence of educational policies aimed at raising awareness of digital education, and the dangers posed by overexposure, may potentiate numerous illicit acts that are extremely detrimental to the fundamental rights of the victim. Pornography of revenge has been growing around the world, including in Brazil, making countless victims, causing moral, psychological and material damages, before the deprivation of their private life, due to the illegal exposure of their intimate and private moments against third parties, reaping even suicide records. The victim, however, finds in the Brazilian legal system adequate framework for its defense, both in the civil sphere, with the forced removal of the content extrajudicially and indemnity for moral and material damages, as in the criminal sphere, hence both the Penal Code and the Statute of the Child and Adolescent have an incriminating response both to punish the offender who improperly captures the intimate image or video of the victim and to the subject who shares privately or privately free material.